Analysis of the Implementation of Adaptive School-Based Management in the Independent Curriculum in West Lombok High Schools - Mohamad Mustari; Muhammad Zubair; Edy Kurniawansyah; Lalu Sumardi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to analyze the implementation of adaptive School Based Management with an independent curriculum in the Schools Mobilizer Program (SMP) education unit. The research employed a descriptive method with a qualitative approach. The research location, namely, 3 high schools implementing the Schools Mobilizer Program (SMP) in West Lombok. The respondents were school principals by were given instruments focused on implementing the Independent Curriculum, SBM, and supporting stakeholders and the obstacles they face. The data sources for this research were secondary data and observation, with the data analysis technique used as qualitative descriptive analysis. The results of this research showed that SBM was still very relevant to the demands of the times and the needs of society, because SBM provides broad autonomy to schools to involve the community to take part in determining school policies. Schools were given independence in managing human resources and financial resources by allocating them according to needs and priorities according to the school's strategic plan and operational plan, as well as developing organizational cultural values based on local wisdom to encourage community participation in order to grow and develop organizational culture and quality culture and form students who have character through the application of the noble values of the community where the school was located in accordance with the independent learning platform.